Occlusion of the small bowel on a virgin abdomen: Case report - Ekuke, Eddy Oleko; Lhaine, Meriem; El Bouhadoutti, Hicham (Journal of Surgery and Medicine, 2018)
Peritoneal flanges on virgin abdomen are of uncommon etiology of occlusive syndrome. In particular, congenital bridles represent 0.7 to 2% of small bowel and colon occlusions, from all causes. We report a case of a pelvic occlusion in a 22-year-old patient.